Macro and Microstructural Characteristics of North Atlantic Deep-Sea Sponges as Bioinspired Models for Tissue Engineering Scaffolding - Martins, Eva; Rapp, Hans Tore; Xavier, Joana R.; Diogo, Gabriela S.; Reis, Rui L.; Silva, Tiago H. (Frontiers in Marine Science, 2021)
Sponges occur ubiquitously in the marine realm and in some deep-sea areas they dominate the benthic communities forming complex biogenic habitats – sponge grounds, aggregations, gardens and reefs. However, deep-sea sponges and sponge-grounds are still poorly investigated with regards to biotechnological potential in support of a Blue growth strategy. Under the scope of this study, five dominant North Atlantic deep-sea sponges, were characterized to elucidate promising applications in human health, namely for bone tissue engineering approaches. Geodia barretti (Gb), Geodia atlantica (Ga), Stelletta normani (Sn), Phakellia ventilabrum (Pv), and Axinella infundibuliformis (Ai), were morphologically characterized to assess macro and microstructural features, as well as the chemical composition of the skeletons, using optical and scanning electron microscopy, energy dispersive x-ray spectroscopy and microcomputed tomography analyses. Moreover, compress tests were conducted to determine the mechanical properties of the skeletons. Results showed that all studied sponges have porous skeletons with porosity higher than 68%, pore size superior than 149 µm, and higher interconnectivity (>96%), thus providing interesting models for the development of scaffolds for tissue engineering. Besides that, EDS analyses revealed that the chemical composition of sponges pointed that demosponge skeletons are mainly constituted by carbon, silicon, sulfur, and oxygen combined mutually with organic and inorganic elements embedded in its internal architecture that can be important features for promoting bone matrix quality and bone mineralization. Finally, the morphological, mechanical, and chemical characteristics here investigated unraveled the potential of deep-sea sponges as a source of biomaterials and biomimetic models envisaging tissue engineering applications for bone regeneration.